Impact of UNESCO Heritage Status on Japanese Food Discourse in Major Japanese Newspapers - Omori, Isami (Advances in Social Sciences Research Journal, 2018)
The aim of this study is to examine the influence of the recent political process, pertaining to the inscription Japanese food (washoku) in the list of Intangible Cultural Heritage by the United Nations Educational, Scientific and Cultural Organization(UNESCO) in 2013 on the food discourse in Japan. The change in the number of articles containing the 3 words for Japanese food, that is, ‘nihonshoku’, ‘nihonryori’, and ‘washoku’, and the appearance frequencies of 50 related words were evaluated in 3 Japanese nation-wide newspapers over a 17-year duration from 2000 to 2016. The appearance ratio of each keyword was analysed for the total number of articles related to Japanese food on a yearly basis. Results showed that the UNESCO inscription triggered a rapid increase in the number of articles related to Japanese food. The highest appearance ratio occurred for the keywords ‘taste’, and ‘heart’, in that order. In addition, ‘culture’, ‘heritage’, ‘world’, ‘abroad’, ‘local’, and ‘tourism’ had high appearance ratios following the UNESCO recognition. Ingredients and seasonings such as rice, fish, and soy sauce had higher appearance ratios than menu or course style names such as ‘sashimi’ and ‘kaiseki’. Results indicate that the UNESCO recognition drew Japanese people’s attention to Japanese food which was hitherto unseen. This is because the UNESCO registration facilitated a contrast between the characteristics of Japanese food and other international cuisines, which enhanced the attractiveness of Japanese food. In addition, the UNESCO recognition linked words associated with time and place to Japanese food. This political process enabled the propagation of a discourse that emphasized the historical continuity of Japanese food as Japanese ‘taste’.